Manuring in Barroso: a crucial farming practice - Portela E. (Strengthening endogenous development patterns in European agriculture, 1993)
In Barroso, sustainable agriculture is based upon diversity of crop and animal nutrient cycling and utilisation of all available endogenous resources. One of these resources is manure. Soil fertility has been improved by application of large quantities of farmyard manure and sheep, goat and pig manure. Barroso farming has not been dependent on large inputs of fertilisers. However, those farmers that had possessed the conditions for higher crop intensification are increasingly applying larger of fertilisers, frequently in inadequate quantities or inefficient proportions of nutrients. A more efficient fertiliser-use (energy consuming) could be reached if more was known about the local manure. Manure have a lot to do with the farmers' conditions of work, with energy saving and with ecologically sound agriculture. The paper reviews available data on manuring and fertilisation and presents some hypotheses to explain that puzzling farming practice. Finally the main constraints for the maintenance of manuring practices are discussed.
Seminar on 'Strengthening Endogenous Development Patterns in European Agriculture', 1992/10/20-22, Chania (Greece)